2008
DOI: 10.1117/12.823751
|View full text |Cite
|
Sign up to set email alerts
|

Flow instability induced by spiked bodies

Abstract: In order to investigate the unsteady flow field around a spiked body in supersonic flow, time-resolved color schlieren visualization was applied using a high-speed video camera which could take up to 1 000 000 frames per second at full frame resolution. Conically and spherically tipped spikes of six different lengths could be attached at the center of the model and their effect on the flow unsteadiness was visually observed. The obtained images revealed in great detail the interaction between the incoming free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As already mentioned in [18], the air around the spike does not withstand the pressure of the incoming flow as the wider shock layer allows the high-pressure gas to escape around the shoulder of the cylinder. The flow then pushes the bow shock back towards the model and a conical flow pattern is formed once again at the tip of the spike (Figure 9).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As already mentioned in [18], the air around the spike does not withstand the pressure of the incoming flow as the wider shock layer allows the high-pressure gas to escape around the shoulder of the cylinder. The flow then pushes the bow shock back towards the model and a conical flow pattern is formed once again at the tip of the spike (Figure 9).…”
Section: Resultsmentioning
confidence: 93%
“…Former studies about spike-tipped models pointed out [15][16][17][18] the interaction between the incoming free stream flow and the high-pressure region near the model, which could have an influence on upstream at the tip of the spike by displacing the boundary layer along the spike and subsequently inducing a large-scale instability of the flow. In this paper, the unsteady flow around a spiketipped model at Mach number 3 is studied.…”
Section: Introductionmentioning
confidence: 99%
“…Feszty et al [93,94] confirmed using the numerical simulations the findings of Kenworthy. A high quality flow visualization for pulsation mode can be found in [95]. Sahoo et al [66] confirmed experimentally that rounding the spike tip can change pulsation mode into oscillation one.…”
Section: Key Studies On Flow Unsteadiness Associated With Mechanical mentioning
confidence: 96%